Theatre its art and craft - Gendrich, Cynthia M. 1952-; Archer, Stephen M. (Rowman & Littlefield, 2017)
"Theatre: Its Art and Craft is an introductory theatre text that focuses on the practitioners and their processes. Using an accessible tone and a focused exploration of how theatre artists work, the book covers every aspect of this art form: from writing, directing, and acting to the designing of sets and costumes, as well as the use of props, lights, sound, and new technology. This book also examines the varying roles of scholars, critics, and dramaturgs. This seventh edition has been thoroughly revised and features new statistics, new photos, and updated references. New sidebars have been added throughout, including one on cultural appropriation, another on lighting technology, and more and better discussions of what carpenters, technical directors, stage managers, and theatre artists do"--Provided by publisher.